Replication data for: Interactions between winter and summer herbivory affect spatial and temporal plant nutrient dynamics in tundra grassland communities - Petit Bon, Matteo; Inga, Katarina Gunnarsdotter; Jónsdóttir, Ingibjörg Svala; Utsi, Tove Aagnes; Soininen, Eeva Marjatta; Bråthen, Kari Anne (DataverseNO, 2020)
Data used to answer the question: To what extent herbivore interactions affect tundra plant-community nutrient levels during the short duration of an alpine/sub-Arctic summer